The effect of lower limb training on muscular support of the knee and risk of anterior cruciate ligament injury - Cochrane, J.; Lloyd, D.; Ackland, T.; Besier, T.; Elliott, B. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
An intervention study was performed to investigate the effect of lower-limb training programs on knee muscle activation patterns and their potential to support the knee load during running and cutting manoeuvres. It is known that balance training can reduce ACL injury but the underlying mechanisms are unknown. The effects that strength training has on support for the knee joint during sporting manoeuvres are also not known. Analysis of activation levels and patterns of leg muscles during running, sidestepping and crossovercutting manoeuvres prior to and following 12-week training programs revealed important results in terms of potential support of load on the ACL. Balance training increased cocontraction and supportive muscle activation patterns, as did the combination of machine and balance training to a lesser extent. The strength training programs tended to reduce co-contraction and were associated with changes which would lead to less stability of the knee during sporting manoeuvres. It is recommended that balance training should be implemented to reduce an athleteÆs risk of ACL injury.